Speciesspecific PCR primers for Guignardia citricarpa and Guignardia mangiferae - Everett, K.R.; Rees-George, J. (New Zealand Plant Protection, 2006)
The plant pathogen Guignardia citricarpa causes citrus black spot and is not considered to be present in New Zealand Speciesspecific polymerase chain reaction (PCR) primers were designed to identify G citricarpa and G mangiferae a closely related saprotroph that is present in New Zealand These PCR primers were tested against a range of other saprotrophic and pathogenic fungi viz Botrytis cinerea Botryosphaeria dothidea B parva Cladosporium sp Colletotrichum acutatum C gloeosporioides Cryptosporiopsis sp Epicoccum sp Nigrospora sp Penicillium sp Pestalotia sp Phialophora sp Phlyctema sp Phoma sp Phomopsis sp Stemphylium sp and Venturia inaequalis The primers JRGGc were specific to G citricarpa and JRGGm to G mangiferae A 226 bp product was amplified from G mangiferae DNA using JRGGm primers and a 501 bp product was amplified from G citricarpa DNA using JRGGc primers These primers thus distinguished G citricarpa from G mangiferae and can be used to rapidly identify incursions by citrus black spot